COVID-19 Isolation Home Exercise Gone Wrong. A Case Report (Revista de Medicina Clinica, 2020)
Introduction: Since the emergence of the coronavirus disease (COVID-19) and the implementation of preventive measures for its contention such as the closure of sports facilities, gyms, and parks along with general lockdown, people have been in need of staying active at home. Accidents due to physical activity in quarantine are increasing, especially without adequate knowledge on techniques and correct prescription of exercise. Case Report: We present the case of a physically active 30-year-old male who referred having an accident due to the misuse of elastic resistance bands during his home workout. He suffered head trauma and ocular injury with hemovitreous and significant decrease in visual acuity with retinal detachment suspicion. Discussion: The importance of adequately executing any exercise and knowing about safety measures is vital, especially in these isolation times where both physical and mental health must be sought, as well as avoiding saturation of emergency rooms with preventable accidents. Conclusion: As health providers, we must guide people in a proper way to stay active despite the isolation, as well as provide safety counseling on injury prevention.
Keywords: COVID-19; resistance exercise; closed globe injury